Studies in rust fungi VIII - Patil, Anjali; Dangat, Bhaurav; Patil, Mansaram (International Journal of Biological Research, 2014)
Two rust fungi Puccinia iphigeniae sp. nov. collected on Iphigenia pallida Baker (Liliaceae) and Uromyces euphorbiae Cooke and Peck var. euphorbiicola (Tranz.) Arthur on the leaves of Euphorbia thymifolia L. and E. chemaesyce L. have been described in the present article. Puccinia iphigeniae sp. nov. is a new species and Uromyces euphorbiae Cooke and Peck var. euphorbiicola (Tranz.) Arthur is a nomenclatural change. Keywords: Rust, Puccinia, Uredinales, Uromyces.